2017
DOI: 10.1002/mmce.21211
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and reduction methods of specific absorption rate for biomedical applications: A survey

Abstract: Specific Absorption Rate (SAR) is an inevitable parameter to be considered for various RF dosimetry evaluations in the field of biomedical engineering. There is a much concern in exposure studies as they have a significant impact on the social and health issues in the recent global community. SAR measures the absorption of electromagnetic radiation of RF from devices in an exposure area. The significance of SAR parameter has been awakened in broad areas of technology and even considered in the design of radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…The SAR characteristics are observed on human head and on arm and the corresponding obtained figures are plotted in Figure for three operating frequencies at 3.6 GHz, 4GHz, 7.2 GHz, 8GHz, and 10.5 GHz. As per FCC the SAR should be 1.6 W/Kg averaged over 1 g of tissue . As per IEEE and ICNIRP the SAR values are 2 W/Kg averaged over 10 g of tissue and 1.6 W/Kg for 1 g of tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAR characteristics are observed on human head and on arm and the corresponding obtained figures are plotted in Figure for three operating frequencies at 3.6 GHz, 4GHz, 7.2 GHz, 8GHz, and 10.5 GHz. As per FCC the SAR should be 1.6 W/Kg averaged over 1 g of tissue . As per IEEE and ICNIRP the SAR values are 2 W/Kg averaged over 10 g of tissue and 1.6 W/Kg for 1 g of tissue.…”
Section: Resultsmentioning
confidence: 99%
“…As per FCC the SAR should be 1.6 W/Kg averaged over 1 g of tissue. 22 As per IEEE and ICNIRP the SAR values are 2 W/Kg averaged over 10 g of tissue and 1.6 W/Kg for 1 g of tissue. The obtained results of the current antenna are satisfying the standards and the observed values are tabulated in Table 3.…”
Section: Antenna Placed On the Human Bodymentioning
confidence: 99%
“…According to International Commission on Non-Ionising Radiation Protection (ICNIRP) guidelines, the maximum acceptable SAR level on human body is 1.6 W/kg. An extensive literature survey on several techniques and materials for SAR reduction are discussed in [24,25]. In recent years, electromagnetic metamaterials have been used widely for SAR reduction in the design of antennas [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In [3], their study found that low-dose ionizing radiation exposure affects cognitive skills in exposed children later in life. It is reported that high doses of ionizing radiation to the head (20 -50 Gy) lead to severe learning and memory impairment which is characteristic for Alzheimer's at old age [4] [5]. It is reported in [6]…”
Section: Introductionmentioning
confidence: 99%